2011
DOI: 10.1111/j.1600-0838.2009.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting autologous blood transfusions: a comparison of three passport approaches and four blood markers

Abstract: Blood passport has been suggested as an indirect tool to detect various kinds of blood manipulations. Autologous blood transfusions are currently undetectable, and the objective of this study was to examine the sensitivities of different blood markers and blood passport approaches in order to determine the best approach to detect autologous blood transfusions. Twenty-nine subjects were transfused with either one (n=8) or three (n=21) bags of autologous blood. Hemoglobin concentration ([Hb]), percentage of reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 17 publications
1
74
0
Order By: Relevance
“…One subject was not tested in Phase V, which present mean ± SD for n = 9 only Eur J Appl Physiol (2011) 111:2307-2314 2311 Parisotto et al 2001) or phlebotomy (Damsgaard et al 2006;Morkeberg et al 2009a), and decrease after rhEPO treatment ceases (Gore et al 2003) or blood is reinfused (Morkeberg et al 2009c). Thus anti-doping authorities carefully scrutinise reticulocyte levels for signs of doping.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One subject was not tested in Phase V, which present mean ± SD for n = 9 only Eur J Appl Physiol (2011) 111:2307-2314 2311 Parisotto et al 2001) or phlebotomy (Damsgaard et al 2006;Morkeberg et al 2009a), and decrease after rhEPO treatment ceases (Gore et al 2003) or blood is reinfused (Morkeberg et al 2009c). Thus anti-doping authorities carefully scrutinise reticulocyte levels for signs of doping.…”
Section: Discussionmentioning
confidence: 96%
“…Although the ABP software and z score approach can be tweaked to yield similar outcomes (Morkeberg et al 2009c), this requires that the same between-and within-subject variances be adopted with each of the calculations. This was not done in Borno's study, subsequently, although a theoretical insight, Borno's findings cannot be extrapolated to evaluate the true efficacy of WADA's ABP protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Hbmr (derived from the formula [4.51 ϫ ln (Hb mass ) Ϫ ͌ reticulocyte percentage]; currently not part of antidoping testing) demonstrated superior sensitivity in detecting blood transfusion. 102 The same authors have reported that the determination of the ratio between the mass of Hb in the mature erythrocyte population and in the reticulocyte fraction (RBC Hb /Ret Hb ratio) is the best indicator of autologous blood doping. 103 …”
Section: Rbc Parameters Associated With Autologous Retransfusionmentioning
confidence: 99%
“…Changes in Hb and %ret after transfusion may be difficult to distinguish from normal physiologic variations. 15 At baseline, a well-trained endurance athlete may have an expanded total blood volume of 8 L and a hematocrit of 45%, such that transfusion of a single unit may only make up ϳ 5% of the total RBC pool in circulation. In addition, the almost immediate posttransfusion removal of as much as 25% of the transfused RBCs from circulation limits the potential window of detection of RBCs with storage lesions.…”
Section: Blood Transfusionsmentioning
confidence: 99%